Synthetic polyploid induction influences morphological, physiological, and photosynthetic characteristics in Melissa officinalis L. - Bharati, Rohit; Gupta, Aayushi; Novy, Pavel; Severová, Lucie; Šrédl, Karel; Žiarovská, Jana; Fernández-Cusimamani, Eloy (Frontiers in Plant Science, 2023)
Melissa officinalis L. is a well-known herb widely grown for its numerous industrial and ethnopharmacological properties. Although, there has been a significant lack in the breeding attempts of this invaluable herb. This study aimed to develop novel genotypes with superior agronomical traits using in vitro polyploidization in M. officinalis. Nodal segments were micropropagated and treated with oryzalin at 20, 40, and 60 μM for 24 and 48 hours. With the increasing concentration and duration of oryzalin, the survival rate of the treated explants decreased exponentially. Further, flowcytometry, chromosome counting, and stomatal characteristics were used to confirm the ploidy level of the surviving plants. The highest polyploid induction rate (8%) was observed in treatment where oryzalin was treated at 40 μM for 24 hours. The induced tetraploid plant displayed vigorous growth with larger organs, including longer shoots, larger leaves, and a higher number of leaves per shoot. Evaluation of chlorophyll content and fluorescence parameters elucidated disparities in photosynthetic performance between the two genotypes. The average essential oil yield in the tetraploid plants increased by 75% compared with the diploid plants due to the significantly larger size of peltate trichomes in the tetraploid plants. Diploid and tetraploid plants contain three major components in their essential oil composition: geranial, neral, and citronellal. While citronellal remained the same, geranial and neral increased by 11.06% and 9.49%, respectively in the tetraploid population. In conclusion, the employed methodology utilizing oryzalin as an anti-mitotic agent for polyploid induction in M. officinalis was effective.The resulting polyploid genotype exhibited various superior morpho-physiological traits. Polyploid lemon balm has the potential to meet commercial demands and contribute to the improvement of lemon balm cultivation.